Power system stability in the Era of energy Transition: Importance, Opportunities, Challenges, and future directions - Ahmed Mohammed Saleh; Vokony István; Muhammad Adnan Khan; Muhammad Waseem; Amgad Naji Ali Ahmed (Energy Conversion and Management: X)
Utilities are struggling to fulfil increased energy demand from domestic and industrial expansion. Conventional energy sources are insufficient to satisfy this burgeoning global energy demand, and the substantial emissions of pollutants associated with these sources are concerns. The energy transition is becoming more inevitable than ever for mitigating this situation. However, this transition threatens the power system stability by introducing intermittent and low inertia energy resources to the grid. In terms of the energy transition, there is abundant research about design purposes, but those considering the power system stability are still inadequate. The significance, opportunities, challenges, and future directions of the energy transition related to power system stability are covered thoroughly in this article. The IEEE 14-bus system is selected as a case study for renewable energy sources (RES) integration as it includes various voltage levels (132, 33, and 0.4) kV. Various scenarios of RES integration, fault, sudden change of generation and load are simulated using DIgSILENT /MATLAB software. The case study clarifies how power system stability is affected by the energy transition and how the energy storage system improves stability. It also discusses the future direction as a baseline for scholars and industries to accelerate the smooth energy transition.